High quality speech codec employing sines + noise + transients model - Maciej Kulesza; Ł. Litwic; G. Szwoch; A. Czyżewski (Archives of Acoustics)
A method of high quality wideband speech signal representation employing sines+transients+ noise model is presented. The need for a wideband speech coding approach as well as various methods for analysis and synthesis of sines, residual and transient states of speech signal is discussed. The perceptual criterion is applied in the proposed approach during encoding of sines amplitudes in order to reduce bandwidth requirements and to preserve high quality of speech. Therefore, the psychoacoustic model devised for perceptual speech coding is presented. The experimental results reveal that method for tonality estimation employed in the psychoacoustic model has a significant impact on perceptual coding accuracy. Various methods for tonality estimation are presented and compared.